Managing Education in a Recessed Economy: A Psychological Perspective on Secondary School Students in Rivers State: An Imperative Analysis - Patricia Melchizedek Ogonda; Osilem Okachiku Agbaraeke (International Journal on Integrated Education, 2026)
The persistent economic recession in Nigeria continues to exert immense pressure on the education sector, particularly at the secondary school level. This paper presents a psychological perspective on managing education in a recessed economy, with a specific focus on secondary school students in Rivers State. It argues that economic hardship not only disrupts the financial operations of schools but also deeply affects the emotional, cognitive, and behavioral well-being of learners. Based on psychological theories including Maslow’s Hierarchy of Needs, Bronfenbrenner’s Ecological Systems Theory and Theory of Emotional Resilience, it elaborates on how the economic crisis decreases students’ ability to learn, adapt and prosper in school settings. This document argues that present educational anticipatory responses to recession are primarily bureaucratic and fiscal, ignoring the psychological context mechanisms that directly affect students engagement, motivation, and behaviour. Chronic stress owing to food insecurity, jobless parents, dilapidated school facilities and emotional turbulence, which erode learning ability and encourage detachment — these are the pressures often faced by students. The paper calls for a paradigmatic shift in educational management that grounds a set of psychological considerations within policy, planning and practice. They include psycho-social support structures built into schools, training teachers in emotional intelligence and trauma-informed pedagogy, and investment in mental health services by government. The paper concludes that education management in a recession-struck economy must span much further than infrastructure and budget, and rather as a very deliberate psychology from many stakeholders and partners in order to protect the wellbeing and sustainable results of learners. The paper adds to the global discourse around education systems that are inclusive, resilient and responsive by providing a strategic and psychological perspective to management of education in crisis.